Development of Interactive E-LKPD Based on Socio Scientific Issues (SSI) on Renewable Energy Material to Facilitate Students' Critical Thinking - Atifah Alya Ramadhina Agustin; Asep Saefullah; Rahmat Firman Septiyanto (JURNAL PEMBELAJARAN FISIKA, 2025)
The lack of critical thinking skills among students is one of the causes of Indonesia's low science literacy score in PISA 2022. Socio Scientific Issues (SSI) learning can improve these skills by linking renewable energy material through real issues. With the SSI approach, this E-LKPD is expected to make physics learning more interesting and relevant through daily life, so that students can be more actively involved in the learning process and develop their critical thinking skills. This study aims to determine the results of material and media expert validation of E-LKPD and determine student readability of E-LKPD. The research method used is R&D (Research and Development) with the 4D research model, namely define, design, develop and disseminate. E-LKPD was developed in digital form through liveworksheet and validated by material experts, media experts, and tested for readability by students. The results of the material expert validation resulted in a percentage of 92.9%, which was categorized as very feasible; and the results of the media expert validation resulted in a percentage of 89.7%, which was also categorized as very feasible. The student readability test of the E-LKPD of 91.3% was classified as high.